Thiophene-fused aromatic belts - Shudo, Hiroki; Wiesener, Philipp; Kolodzeiski, Elena; Mizukami, Kiichi; Imoto, Daiki; Mönig, Harry; Amirjalayer, Saeed; Sakamoto, Hirotoshi; Klaasen, Henning; Ravoo, Bart Jan; Kimizuka, Nobuo; Yagi, Akiko; et al. (Nature Communications, 2025)
Aromatic belts, ultrashort carbon nanotubes, and related structures, are emerging molecular entities in the fields of organic electronics and supramolecular chemistry owing to their structural rigidity, fully fused π-conjugation, and well-defined cavity. Synthesis of aromatic belts with embedded thiophene structures, which manifest significant optoelectronic and conductive properties, has not yet been achieved. Herein, we report the synthesis of thiophene-fused aromatic belts (thiophene belts) via one-step sulfur cross-linking reaction of partially fluorinated cycloparaphenylenes. Their structural features, including unidirectional columnar stacking with high dipole moment in crystals, two-dimensional layer assembly on metal surfaces, and photophysical properties, such as long-lifetime phosphorescence, are uncovered. These distinctive features of the thiophene belts should inspire a range of applications such as optoelectronic devices and polar materials.